UJI TOKSISITAS EKSTRAK METANOL DARI BUAH SIRIH HIJAU (Piper betle. L) - Ester Rampa; Rini Prastyawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2016)
Studies have been conducted toxicity tests methanol extract of the fruit green betel (Piper betle. L). The purpose of this study was to determine the toxicity (LC50) methanol extract of the fruit green betel (Piper betle L.). Samples are green betel fruit botanicals as much as 150 grams. The study begins with the extraction of crude of sample maceration using methanol solven. Determination of toxicity tests carried out with BSLT (Brine Shrimp Lethality Test). Data were analyzed using the percentage of larval mortality probit analysis with MINITAB version 13.2 programs with 95% confidence interval in order to obtain the LC50 values. Results of research betel fruit methanol extract of green indicate LC50 values of 309.17 ppm potential as an antimicrobial for toxic.